Prevalence and Changing Trend of Dengue in a Tertiary Care Hospital in Southeastern Rajasthan - Rana, Jyoti (Eastern Journal of Medical Sciences, 2026)
Background: Dengue is a major mosquito-borne viral disease with increasing incidence in India, showing marked seasonal and year to-year variation. Southeastern Rajasthan has experienced recurrent outbreaks, highlighting the need for continuous surveillance.   Aim: To determine dengue seropositivity by NS1 antigen and anti- dengue IgM antibody detection through ELISA, and to correlate  the results with evolving epidemiological trends. Materials and Methods: A cross -sectional study done from November2021 to  April 2024 with blood samples tested from clinically suspected cases of dengue virus infection.  Results: Out of 652 samples tested,  215 (32.97%) were positive. Seropositivity was highest in 2021–22 (47.0%), declined in 2022–23 (13.37%), and resurged in 2023–24  (36.77%). The most affected age group was 16–30 years, with predominance during the post-monsoon season and higher positivity in  rural areas. Conclusion: Prevalence of dengue seropositive cases was 55 (47.00%) in 2021- 2022 it was 22 (13.37%) in 2022-2023, in 2023-2024 was 138(36.77%) indicating fluctuating trends of dengue transmission, with an initial peak, a significant decline, and a subsequent resurgence.